PERLINDUNGAN HUKUM ATAS DATA PRIBADI BAGI KONSUMEN DALAM KLAUSULA EKSONERASI TRANSPORTASI ONLINE - Rizal, Muhammad Saiful; Yuliati, Yuliati; Hamidah, Siti (Faculty of Law, University of Muhammadiyah Malang, 2019)
The exoneration clause is still used in the online transportation agreement clause, when the user registers. This has an impact on the legal uncertainty for consumers in the protection of their personal data managed by the application business actors. This study aims to analyze the presence or absence of violations in Article 18 of the Consumer Protection Law related to exoneration clauses in online transportation, and forms of legal protection of consumer personal data in standard contracts. This research is a normative legal research, with a statue approach and comparative approach. The results of this study are that application business actors have transferred the responsibility of protecting consumer personal data which should be the obligation of the application business actor. The application of exoneration clauses carried out by application businesses is very detrimental to consumers by feeling insecure and comfortable in using online transportation services. Forms of legal protection from the government related to consumer personal data in using online transportation services with the obligation of businesses to revise and replace losses suffered by consumers.